2019
DOI: 10.1002/aqc.3116
|View full text |Cite
|
Sign up to set email alerts
|

Natural and anthropogenic drivers of foraging behaviour in bottlenose dolphins: Influence of shellfish aquaculture

Abstract: 1. In the coastal environment, marine mammals are exposed to one of the fastest growing food production sectors; namely, the shellfish farming industry. Identification of critical habitats, such as foraging grounds in highly human-impacted areas, is essential to species conservation. Therefore, understanding the variables that influence a species' foraging behaviour is important for their conservation, especially for long-lived mammals such as cetaceans. 2. The aims of this study were (a) to identify and quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 64 publications
(90 reference statements)
0
11
0
Order By: Relevance
“…Seal abundance was the same at sites with and without mussel farms, and no negative interactions were reported. Along the northwestern coast of Spain, mussel farms influence habitat uses and foraging behaviour of bottlenose dolphins 91,92 . The shellfish culture method may impact animals differently due to the gear configurations and materials used.…”
Section: Protected Species and Marine Aquaculturementioning
confidence: 99%
See 1 more Smart Citation
“…Seal abundance was the same at sites with and without mussel farms, and no negative interactions were reported. Along the northwestern coast of Spain, mussel farms influence habitat uses and foraging behaviour of bottlenose dolphins 91,92 . The shellfish culture method may impact animals differently due to the gear configurations and materials used.…”
Section: Protected Species and Marine Aquaculturementioning
confidence: 99%
“…Along the northwestern coast of Spain, mussel farms influence habitat uses and foraging behaviour of bottlenose dolphins. 91,92 The shellfish culture method may impact animals differently due to the gear configurations and materials used.…”
Section: Mussel Farmsmentioning
confidence: 99%
“…When dolphins were sighted, searching effort ceased and the vessel slowly maneuvered toward them to minimize possible disturbance during approach. A group of bottlenose dolphins was de ned as one or more individuals observed within a 100-m radius and, if more than one, interacting with each other and performing the same behavioural activity (Methion and Díaz López 2019). At least two observers with digital SLR cameras equipped with telephoto lenses attempted to photograph both sides of the dorsal n of each dolphin of the group.…”
Section: Data Collectionmentioning
confidence: 99%
“…Bottlenose dolphins (Tursiops spp. ), despite being widely considered some of the most adaptable of the world's cetaceans, are highly susceptible to environmental changes (Bejder et al 2006;Sprogis et al 2018;Díaz López 2019;Methion and Díaz López 2019). Due to their inshore distribution and life history characteristics (i.e., relatively large size, slow growth, late maturation, long gestation period, single births at a time, and long calving interval), bottlenose dolphins are vulnerable to a range of anthropogenic impacts such as habitat modi cation, over shing, noise and chemical pollution, bycatch, and boat strikes (Díaz López 2006;Wang and Yang 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A meta‐analysis of the impacts of marine and freshwater aquaculture found that aquaculture facilities attract a variety of species, particularly wild fish, which were found to be on average 1.2× larger and 1.7× heavier than fish from reference sites; marine mammals showed no consistent response to the presence of aquaculture facilities, though pinnipeds were found to experience higher mortality from aquaculture facilities due to culling and entanglement (Barrett, Swearer, & Dempster, 2019). Bottlenose dolphins ( Tursiops truncates ) off the northwestern coast of Spain, however, were found to forage predominantly inside shellfish farming areas, with such behavior correlated to both environmental conditions (sea surface temperature and time of day) and the presence of shellfish farms (Methion & Lopez, 2019).…”
Section: Effects Of Fishing and Aquaculturementioning
confidence: 99%